Kepuasan Wisatawan Sebagai Indikator Kunci dalam Meningkatkan Daya Saing Pariwisata Bangka Belitung - Gustian Audi; Lestari Lestari; Indah Noviyanti (Global Leadership Organizational Research in Management, 2025)
Tourism is a sector that contributes significantly to economic growth in Bangka Belitung. This article explores the level of visitor satisfaction as a key indicator in improving the competitiveness of the tourism sector in this region. This study applies a mixed approach, combining quantitative methods to gain in-depth insights into the factors that influence visitor satisfaction. Through a survey involving 100 respondents who visited various destinations in Bangka Belitung, the results show that service quality, natural beauty, and adequate facilities have a positive effect on tourist satisfaction. High satisfaction not only encourages tourists to return, but also increases word-of-mouth recommendations, which are very important in tourism marketing. In addition, with increased satisfaction, the competitiveness of tourism in this area is also raised, making it more attractive compared to other destinations. This study recommends that tourism managers focus on improving service quality, infrastructure development, and ongoing promotion to attract more tourists. Thus, tourist satisfaction is not only a goal, but also an important strategy in strengthening Bangka Belitung's position as a competitive tourist destination.